Uncovering the Investigator’s Assumptions in Sexual Violence Crime Investigative Interviews: A Forensic Linguistic Analysis - Vidhiasi, Dhion Meitreya (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: The information supplied by a victim of sexual violence during an investigative interview frequently serves as the sole foundation for investigators in processing a sexual violence case. Nonetheless, the investigative interview process often lacks professionalism due to efforts to impose the investigator’s personal assumptions. Aims: This research is a forensic language analysis intended to uncover the assumptions held by an investigator during an investigative interview with a child victim of sexual violence. Methods: This study utilized qualitative data obtained from the investigative interview between an investigator and a child victim of sexual violence at a police station in Cilacap. Conversation data were collected using listening and note-taking techniques. The statistics were subsequently verified with the investigator to validate their legitimacy. This study employs the dialogic speech act theory technique proposed by Weigand (2010) to elucidate the assumptions held by the researcher. Results: The findings of this study suggested that the investigator attempted to impose her personal assumptions on the victim through numerous exploratory speech acts designed to validate, offer options, and direct the victim’s responses. Implications: The findings of this study may serve as a reference in assessing the specifics of inquiries within the Standard Operational Procedure on Examination and questioning techniques during the investigative interview procedure.